:5b^2+(3-2b)(3+2b), (3a-1)(3a+1)-17a^2, (2a+b)(4a^2+b^2)(2a-b), (3m-2)(3m+2)+4, (5a-3c)(5a+-a)(7c+a), (4b+10c)(10c-4b)+(-5c+2b)(5c+2b), (c+b)(c--b^2). , , это важно! с вопросами в комменты.

hfyfghhvu hfyfghhvu    3   28.07.2019 00:30    2

Ответы
рпрпрп1 рпрпрп1  25.09.2020 15:17
5b^2+(3-2b)(3+2b)=5b^2+9-4b^2=9+b^2
 (3a-1)(3a+1)-17a^2=9a^2-1-17a^2=-8a^2-1
(2a+b)(4a^2+b^2)(2a-b)=(4a^2-b^2)(4a^2+b^2)=16 a^4-b^4
 (3m-2)(3m+2)+4=9m^2-4+4=9m^2
 (5a-3c)(5a+3c)-(7c-a)(7c+a)=(25a^2-9c^2) -(49c^2-a^2)=25a^2-9c^2 -49c^2+a^2=26a^2-58c^2

(4b+10c)(10c-4b)+(-5c+2b)(5c+2b)=( 100 с ^2-16b^2)+(-  25 c^2+4b^2)=75c^2-12b^2
 (c+b)(c-b)-(5c^2-b^2)=c^2-b^2-5c^2+b^2=-4c^2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра